Kritik terhadap Dominasi Eksekutif dalam Politik Anggaran: Tinjauan Teori Pemisahan Kekuasaan - Atmari, Atmari (Universitas Gajah Putih, 2026)
This study aims to critically examine the dominance of the executive in the budget political process in Indonesia through a normative-doctrinal approach. The main focus lies in the analysis of the conformity of state budgeting practices with the principle of separation of powers and the checks and balances mechanism in the presidential system. Budget politics should ideally be a space for a fair distribution of power between the executive and the legislature. However, the reality on the ground shows that there is a tendency to centralize power in the hands of the executive, from the planning stage, discussion, to budget implementation. Through an examination of the 1945 Constitution and related laws and regulations, such as Law No. 17 of 2003, Law No. 23 of 2014, and Law No. 25 of 2004, this study finds that normatively the Indonesian legal system has provided a mechanism for legislative supervision and involvement. However, weak institutional capacity, lack of public participation, and pragmatic political relations make the role of the legislature symbolic. Executive dominance in the budget not only weakens the principles of fiscal democracy, but also has the potential to reduce public accountability to the management of state finances. Therefore, budget political reform needs to be directed at strengthening the legislative oversight function and increasing transparency, so that the budget truly reflects the aspirations of the people, not just the government's agenda.